Exploring the VAW method of writing: the module development - Dg Nursazwani Daud; Wardatul Akmam Din; Asmaa AlSaqqaf (2018)
This  study  intended  to  identify  the  best  learning  strategies  of  writing  by  focusing  in  vocabulary acquisition  among  the  primary  school  pupils  in  Malaysia.  Axiomatically,  local  education  used  the Process  Writing  Approach  in  producing  writing  composition.  Unfortunately,  the  researchers  thought that  it  is  not  sufficient  to  fulfill  the  component  of  good  writing.  By  using  the  theory  of  scaffolding pioneered by Vygotsky, the researchers agreed to include vocabulary learning to scaffold the existing Process  Writing  Approach  followed  by  application  or  practices.  During  application,  the  researcher  as the teacher will provide a module where the experimental group will do writing exercises by using the new  learned  vocabularies.  The  researchers  will  use  mixed  method  research  where  questionnaires  of vocabulary  and  writing  strategies  are  distributed  where  the  results  are  the  determinants  of  VAW module development.